ChemInform Abstract: Low‐Temperature Rh‐Catalyzed Asymmetric 1, 4‐Addition of Arylboronic Acids to α, β‐Unsaturated Carbonyl Compounds. Issue 10 (11th March 2014) - Korenaga, Toshinobu; Ko, Aram; Shimada, Kazuaki
Abstract This is the first example of a Rh‐catalyzed asymmetric 1, 4‐addition below 0°C.